2022
DOI: 10.1038/s41598-021-04557-1
|View full text |Cite
|
Sign up to set email alerts
|

Mott–Hubbard insulating state for the layered van der Waals $$\hbox {FePX}_3$$ (X: S, Se) as revealed by NEXAFS and resonant photoelectron spectroscopy

Abstract: A broad family of the nowadays studied low-dimensional systems, including 2D materials, demonstrate many fascinating properties, which however depend on the atomic composition as well as on the system dimensionality. Therefore, the studies of the electronic correlation effects in the new 2D materials is of paramount importance for the understanding of their transport, optical and catalytic properties. Here, by means of electron spectroscopy methods in combination with density functional theory calculations we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(68 citation statements)
references
References 71 publications
11
51
1
Order By: Relevance
“…Both of them can be represented in hexagonal unit cells (Figure f). Then, every unit cell contains three MPX 3 single layers having D 3 d symmetry (Figure c), which are stacked in a different way . The optical images of the FePS 3– x Se x ( x = 0, 1.5, and 3) bulk crystals and their photographs are shown in the upper row of Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both of them can be represented in hexagonal unit cells (Figure f). Then, every unit cell contains three MPX 3 single layers having D 3 d symmetry (Figure c), which are stacked in a different way . The optical images of the FePS 3– x Se x ( x = 0, 1.5, and 3) bulk crystals and their photographs are shown in the upper row of Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, ,, we have shown that PBE + U + D2 performs very good when studying structures and electronic and magnetic properties of MPX 3 materials, including pristine FePS 3 and FePSe 3 . Here, we employ the same approach to get better insight into the properties of the mixed FePS 1.5 Se 1.5 material under study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, even in this case, the information that is obtained about the electronic structure of the valence band from the VB PE spectra is still very limited. Additional information about the electronic structure of the valence band can be obtained using the method of resonant photoelectron spectroscopy (ResPES), which is especially useful in the study of compounds of transition and rare earth metals—particularly, 3d metals [ 22 , 23 , 24 ]. This method is implemented by measuring the VB PE spectra at photon energies in the vicinity of absorption resonances in the NEXAFS spectrum of an atom of the polyatomic system under study.…”
Section: Introductionmentioning
confidence: 99%